2010
DOI: 10.3758/bf03196690
|View full text |Cite
|
Sign up to set email alerts
|

Visual marking survives graphical change if meaning is retained

Abstract: When some distractors (old items) appear before others (new items) in an inefficient visual search task, the old items are excluded from the search (visual marking). Previous studies have shown that shape changes of static old items are sufficient to eliminate this effect when global luminance is maintained, suggesting that shape identity must be maintained for successful visual marking. It was unclear whether the change in meaning or shape was critical, because these changes were confounded in previous studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…In Experiment 4, search efficiency in the preview condition did not differ from that in the FEB at any display size, indicating that inhibition at the small display sizes was destroyed when the pacmen rotated. This is consistent with the idea that inhibition was applied to the perceptually grouped stimuli and that when their local elements rotated the inhibition was abolished because a perceptually new object identity emerged (Osugi et al, 2010;. Thus, once grouped, the identity of the object as a whole appears to be vital for maintaining an inhibitory template.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In Experiment 4, search efficiency in the preview condition did not differ from that in the FEB at any display size, indicating that inhibition at the small display sizes was destroyed when the pacmen rotated. This is consistent with the idea that inhibition was applied to the perceptually grouped stimuli and that when their local elements rotated the inhibition was abolished because a perceptually new object identity emerged (Osugi et al, 2010;. Thus, once grouped, the identity of the object as a whole appears to be vital for maintaining an inhibitory template.…”
Section: Discussionsupporting
confidence: 84%
“…Previous research has shown that changes to the identity of previewed items can disrupt the preview benefit, whereas changes to surface properties, such as stimulus color or luminance, do not , 2005Watson et al, 2008). Furthermore, Osugi, Kumada, and Kawahara, (2010) showed that even quite large local luminance and shape changes did not abolish the preview benefit provided that the semantic meaning of the items remained the same. Thus, if inhibition is applied to a single representation formed by the spatially grouped elements, local rotation might abolish the preview benefit because the identity of the object would change .…”
Section: Experiments 4: the Influence Of Local Changes To Previewed Stmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, recent studies suggest that the preview benefit remains even when the shape of old items changes, provided that these changes involve either eye blink (Irwin & Humphreys, 2013;von Mühlenen, Watson, & Gunnell, 2013), occlusion (Kunar et al, 2003), or transient masking (Watson & Kunar, 2010). Osugi, Kumada, and Kawahara (2010) demonstrated that preview benefits persist during shape changes if semantic information pertaining to the items is retained. Taken together, this literature points toward a role for top-down processing in the maintenance of preview benefits, despite the presence of disruptive, bottom-up signals (see also Osugi & Kawahara, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Lastly, this account cannot explain the effect of semantic consistency when visual changes to old items occur (Osugi, Kumada, & Kawahara, 2010), the finding that a preview effect occurs when new items are presented during a blink (von Mühlenen, Watson, & Gunnell 2013), or why the detection of new items, carrying the features of old items, is impaired (i.e., the color carry-over effect; Olivers & Humphreys, 2003;Braithwaite, Humphreys, & Hodsoll, 2003, particularly with moving stimuli (Andrews, Watson, Humphreys, & Braithwaite, 2011).…”
Section: Top-down Attentional Inhibitionmentioning
confidence: 99%